The Role of Religious Presuppositions and Precomprehensions in Selecting Narratives Related to the Cause of Revelation (Asbab al-Nuzul) - Dashti, Ali; Akbarnejad, Mehdi; Hosseininia, Mohammad Reza (Jurnal Studi Al-Qur’an, 2019)
Abstract The narratives of the cause of revelation (Asbab al-Nuzul) play a decisive role in the interpretation of Quranic verses. On the other hand, when coming across with these narratives, presuppositions, and precomprehensions play an important role in selecting them. This research tries to study the narratives of the cause of revelation in the Tafsir al Munir fi al Aqidah wa al Shariah wa al Manhaj (by Karya Wahbah al Zuhaili) and explain the role of Wahbah al Zuhaili’s religious presuppositions and precomprehensions in selecting narratives related to the cause of revelation (Asbab al-Nuzul). This study uses library research method that has been discussing the subject with a descriptive-analytical approach. This research shows that in many cases, Wahbah al Zuhaili has been influenced by religious presuppositions and precomprehenstion and has used them to develop his interpretative goals. Keywords: Wahbah al Zuhaili, Tafsir al-Munir, Asbab an-Nuzul